Direitos humanos e tomada de perspectiva social: verificação de um modelo teórico - Feitosa, Izayana Pereira (2013)
Since the promulgation of the Universal Declaration of Human Rights, the subject of rights became part of a fertile field of researches and debates. Some empirical studies have signaled that the concept of human rights depends on the progress of the decision- process perspective of the other, however, such studies didn t focus to verify systematically the existence of this relationship. This thesis aimed to determine the evolution of the conception of HR during human development and if this conception is related to the decision- process perspective. The theoretical approaches adopted were Doise s social psychological perspective on Human Rights plus Piaget and Robert Selman s theories about the decision-process perspective. To accomplish the goal, six studies were proposed during this research. The first study was provided to create items from the Scale of Understanding about Human Rights-SUHR according to four levels of hierarchical conceptions about HR. The second one aimed the psychometric validation of the SUHR and analysis of socio-demographic factors on this scale based on the study about 300 students, divided into 3 age groups: GI=8years old, GII=12 years old and GIII=16 years old, equally distributed according to their sex and the type of their school. The instrument used was the SUHR, a Likert type 5-point scale, in which students pointed out if they understood each of the proposed items, as well as the degree of agreement about them. In SPSS (version 21), descriptive statistics, factor analysis and internal consistency (Cronbach's alpha) were computed. Considering Bartlett's sphericity test, and Kaiser and Cattell s criteria and Parallel Analysis, it was observed that the SUHR presented a factorial organization composed by three dimensions: Guiding principles of humanity, Governing principles of the society and Basic concrete rights revealed the relationship item-factor and the indicators of internal consistency accepted by the statistical literature. Differences were found in the scores of medium scores of age and school integration on levels of understanding of HR. In the third study, were performed a confirmatory factor analysis of SUHR through new data collection in which attended 240 students with similar characteristics to the previous socio- demographic research. In AMOS GRAFICS program, carried out a confirmatory factor analysis; was adopted the ML estimator (MaximumLikelihood) and it was compared to alternative structural models (one factor, two factors and three factors, this one was the expected model) which confirmed the existence of SUHR s three factors which were positively interrelated. The fourth study aimed to develop items related to the stages of social perspective taking to the Scale of Social Decision-Process Perspective-SSDPP. A number of 149 students, aged between 5 and 26 years (Medium age=12,10 years old, SD = 6, 17 %), with 67.3 % of public institutions and 32.7 % of private institutions participated of this study. We used the Dilemma of Olga and the dilemma of the Landless. The answers to the dilemmas were categorized according to the levels of decision-social perspective proposed by Selman. The analysis of the frequencies of responses to the dilemma of Olga revealed significant differences in the age variable, no differences were found for the variables school type and gender. However, the analysis of the frequencies of responses to the plight of landless revealed significant differences in the age and type of school. Based on these analyzes, it was possible to prepare the items for all the stages of making social perspective that made up the instrument. The fifth study, the same students participated in the study and the instrument used was 3 ETPS-scale type Likertde 5 points, in which the students pointed understood if each proposed item, as well as the degree of agreement regarding each. The data collected with the ETPS related to Olga's Dilemma and Dilemma of Landless underwent an AFE following the same criteria used in the analysis of ECDH, however, the factor structure proved confusing and poorly interpreted. Thus, we chose to carry a measure by theory, starting from the theoretical perspective of Selman to assess the structural quality of the scale in question. Regarding the Dilemma of Olga, the AFC indicators revealed that both confirmed Selman's theory about the stages of social perspective taking as the guarantee of a scale capable of measuring these stages. However, the results of the analyses performed with the dilemma of Landless revealed indicators of confirmatory factor analysis under those considered acceptable by the relevant literature. Differences were found in scores of mean scores of age and school integration on levels of decision- process perspective. Finally, in the sixth study, was performed the verification of the desired theoretical model (association between stages of perspective taking to the levels of conceptions of DH). In AMOS 21.0 program, was generated what has been satisfactorily corroborated hypothesized theoretical model. The data were discussed according to theoretical and empirical studies.